Performance analysis of two-way relay cooperation underlay cognitive radio networks based on WIPT - Jisheng XU; Fanzi ZENG; Kang LI; Yongfeng LI (Tongxin xuebao)
The two-way relay cooperation for underlay cognitive radio networks based on WIPT was presented,where secondary system adopted the two-way relay cooperative transmission.First,the relay adopted a power splitting protocol to harvest energy and to decode information transmitted by secondary users,then the relay forwarded information to two secondary users by using the harvested energy.Subsequently the exact expression of the outage probability,the ergodic capacity and energy efficiency of the secondary user system were derived.Finally,numerical simulation discusses the impact on the system performance with regard to secondary transmission power.The results reveal that the two-way relay cooperation effectively reduces the outage probability of data transmission.The capacity and energy efficiency of the system reaches optimal level when the power allocation coefficient is 0.5.